DETERMINING CONSUMER APPEAL OF SELECTED GARDEN STRAWBERRY VARIETIES (FRAGARIA × ANANASSA DUCH.) - Irina V. Luk’yanchuk; Ekaterina V. Zhbanova; Alexander S. Lyzhin (Siberian Journal of Life Sciences and Agriculture, 2022)
Improving the biochemical strawberry fruit composition and aroma is an important goal to develop the assortment of strawberry plants because only a few present-day varieties combine the high quality and aroma in strawberry fruits with increased accumulation of the biochemical composition components. The paper aims to assess hybrid strawberry seedlings based on a range of properties in strawberry fruits to select the most promising genotypes. Strawberry aroma and its consumer appeal were evaluated organoleptically. The biochemical component was tested in the laboratory according to standard methods, and the strawberry aroma was evaluated using DNA markers.